Supply Chain Integration and Employee Productivity in Maritime Firms in Nigeria (London Journal of Research In Management & Business, 2025)
This study investigated the effect of Supply Chain Integration (SCI) on Employee Productivity (EP) in maritime firms in Delta State, Nigeria. The study focused on three dimensions of SCI: Supply Chain Integration Index (SCII), Internal Integration (II), and External Integration (EI), examining how each relates to employee productivity outcomes in a developing regional context. The study was anchored on the Productivity Theory. A descriptive survey research design was adopted. The population of the study comprised 9,540 employees from selected maritime firms, with a sample size of 370 determined using Morgans table. Out of the 370 questionnaires distributed, 293 were validly returned, representing a response rate of 79.19%. The research instrument was a structured questionnaire validated by experts and tested for reliability, yielding a Cronbachs alpha coefficient of 0.79. Data collected were analyzed using descriptive statistics, Pearson correlation, and multiple regression techniques. Findings revealed that SCII and II have significant positive effects on employee productivity, while EI showed a negative but significant effect. Specifically, the regression analysis showed that II had the strongest positive influence on EP (? = 0.749, p< 0.01), followed by SCII (? = 0.227, p< 0.01), while EI had a negative coefficient (? = -0.183, p< 0.05), suggesting possible inefficiencies or trust deficits in external collaboration. It recommends targeted investment in internal systems, enhanced collaboration across departments, and more strategic external partnerships. The findings provide practical insights for policymakers and organizational leaders seeking to optimize employee output through integrated supply chain strategies in similar developing economies.
Keywords: Chinese corporate tax system; Foreign investment; Export of Chinese products; sustainability; technology; 21st-century; innovation; CSR; Supply Chain Integration; Employee Productivity; Internal Integration; External Integration; Maritime Firms.